1943
DOI: 10.1021/ja01243a003
|View full text |Cite
|
Sign up to set email alerts
|

α,β-Unsaturated Aminoketones. VIII.1 Reaction of Primary Amines with 1,3-Diketones and Bromine Derivatives of Benzalacetophenone. Ethylene Imines

Abstract: Vol. 65 2. N-Methylbenzylamine, an open chain type of secondary amine, has been found to react with bromine derivatives of benzalacetone and ben-zalacetophenone in a manner similar to that of heterocyclic secondary amines. Lincoln, Nebraska

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
3

Year Published

1964
1964
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 0 publications
1
22
0
3
Order By: Relevance
“…20 Hydrogen-deuterium exchange in CH 3 OD afforded the partially deuterated compounds whilst tritiated water 5 Ci ml 1 was used to produce the corresponding tritiated compounds. Exchange in a mixture of CH 3 OD and CH 3 OT or DTO afforded a one-step procedure for providing the doubly labelled compounds.…”
Section: Methodsmentioning
confidence: 99%
“…20 Hydrogen-deuterium exchange in CH 3 OD afforded the partially deuterated compounds whilst tritiated water 5 Ci ml 1 was used to produce the corresponding tritiated compounds. Exchange in a mixture of CH 3 OD and CH 3 OT or DTO afforded a one-step procedure for providing the doubly labelled compounds.…”
Section: Methodsmentioning
confidence: 99%
“…Elemental analyses were performed on a CEST 1106 instrument. Mass spectra were recorded on a JOEL DX 303 HF spectrometer with a MASPEC system (MSW/9629) All the (E)-3-arylidene-4-chromanones [9] and aziridine [22] reported here were prepared as per the literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…
by bromination of the related α,β-unsaturated carbonyl compounds, followed with the reaction of ammonia solution [5][6][7][8][9][10].Another synthetic pathway for the synthesis of aziridinyl ketones involves formation of β-hydroxyamino derivatives followed by treatment with either metal alcoholates, or hydroxylamine hydrochloride and then potassium hydroxide [11][12][13][14]. It has been reported the interaction of unsaturated ketones with N-tosyliminoaryliodinanes in the presence of mono-valent copper complexes produces the related aziridinyl ketone [15,16].

It was also reported that oximes could be converted into N-unsubstituted aziridines by treatment with Grignard reagents or by reduction with lithium aluminum hydride in certain cases [17].

3,3-Pentamethyleneoxaziridine can transfer its NH group to electron-deficient olefins to give N-unsubstituted aziridines in low yields [17,18].

…”
mentioning
confidence: 99%
“…by bromination of the related α,β-unsaturated carbonyl compounds, followed with the reaction of ammonia solution [5][6][7][8][9][10].…”
mentioning
confidence: 99%